Can States Withhold Information about Alleged Human Rights Abuses on National Security Grounds? Some Remarks on the ECtHR Judgments of Al-Nashiri v. Poland and Husayn (Abu-Zubaydah) v. Poland (Polish Yearbook of International Law, 2016)
The judgments delivered by the European Court of Human Rights in Al-Nashiri v. Poland and Husayn (Abu Zubaydah) v. Poland highlight the potential tension that may arise between states’ broad reliance on national security grounds to withhold disclosure of secret files and compliance with their obligations under the European Convention on Human Rights. The present article examines the above-mentioned judgments, focusing, in particular, on how (and to what extent) the withholding of secret information may infringe on the right to the truth and, as far as proceedings before the European Court of Human Rights are concerned, the state’s duty to cooperate with it.